Biomass for residential and commercial heating in a remote Canadian aboriginal community. (February 2016) - Stephen, James D.; Mabee, Warren E.; Pribowo, Amadeus; Pledger, Sean; Hart, Randy; Tallio, Sheldon; Bull, Gary Q.
Abstract: Most residents of Canada's 300 remote communities do not have access to natural gas and must rely upon higher cost and/or less convenient heat sources such as electric heat, heating (furnace) oil, propane, and/or cord wood. This research sought to determine the techno-economic feasibility of increasing biomass utilization for space and hot water heating in remote, off-grid communities in Canada and abroad using a two-option case study approach: 1) a district energy system (DES) connected to a centralized heat generation energy centre fuelled by wood chips; and 2) a decentralized heating option with wood pellet boilers in each individual residence and commercial building. The Nuxalk First Nation Bella Coola community was selected as a case study, with GIS, ground surveys, and climate data used to design DES routes and determine heat demand. It was determined that biomass has the potential to reduce heat costs, reduce the cost of electricity subsidization for electrical utilities, reduce greenhouse gas emissions, and increase energy independence of remote communities. Although results of the analysis are site-specific, the research methodology and general findings on heat-source economic competitiveness could be utilized to support increased bioheat production in remote, off-grid communities for improved socio-economic and environmental outcomes. Highlights: Canada has 300 remote communities that rely on diesel for electricity generation. Heat in remote communities is a mix of heating oil, propane, electric, and firewood. Biomass district energy and residential boiler options were compared with baseline. Bella Coola, BC was used as a case study site. Biomass district energy could be an option but residential boilers is lower risk.